Znaczenie banku spółdzielczego dla społeczności lokalnej - Kawa, Marta; Miś, Teresa (Significance of the Cooperative Banks for Local Community, 2006)
Cooperative banks are very closely connected to local communities, thus contributing to their development. Cooperative banks nowadays are often facing difficulties which result from new banking services that have emerged during recent years, the implementation of information technologies, the increasing competition in banking, as well as the necessity of adjusting the norms of banking services to European Union standards.The necessary condition for sustaining their existence and development is the increase in effectiveness, meeting the competition, and satisfying the customers expectations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 401-406